2021
DOI: 10.1519/jsc.0000000000003331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Resistance Training Program on Arterial Stiffness: A Randomized Controlled Trial

Abstract: Werner, TJ, Pellinger, TK, Rosette, VD, and Ortlip, AT. Effects of a 12-week resistance training program on arterial stiffness: a randomized controlled trial. J Strength Cond Res 35(12): 3281–3287, 2021—Arterial stiffness is an indicator of disease and is an independent predictor of cardiovascular events. Some reports indicate that resistance training increases indices of arterial stiffness, whereas others report no association. This study sought to determine the association between 2 common resistance trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Different modes of aerobic exercise training alone for 8-12 weeks (swimming, stair climbing, and all-extremity ergometry) have been shown to significantly decrease arterial stiffness in postmenopausal women and older adults [24][25][26], whereas high-intensity interval training and resistance training for 8-12 weeks showed no differences in arterial stiffness in similar populations [26,27]. Furthermore, CRAE training for 12 weeks has been shown to reduce arterial stiffness in postmenopausal women [13,28].…”
Section: Arterial Stiffness and Blood Pressurementioning
confidence: 99%
“…Different modes of aerobic exercise training alone for 8-12 weeks (swimming, stair climbing, and all-extremity ergometry) have been shown to significantly decrease arterial stiffness in postmenopausal women and older adults [24][25][26], whereas high-intensity interval training and resistance training for 8-12 weeks showed no differences in arterial stiffness in similar populations [26,27]. Furthermore, CRAE training for 12 weeks has been shown to reduce arterial stiffness in postmenopausal women [13,28].…”
Section: Arterial Stiffness and Blood Pressurementioning
confidence: 99%
“… Cortez-Cooper et al (2005) also reported that arterial stiffness and wave reflection increased following 11-week high-intensity resistance training (12 exercise, up to 6 sets per session) in young women. By contrast, Werner et al ( Werner et al, 2019 ) observed that the arterial stiffness indices exhibited no changes following 12 weeks of high-intensity and high-volume resistance training (9 exercise, 2–3 sets, and 3–4 sets, respectively) in young men. The findings of this study are in agreement with the results of Au et al (2017) , who found a decrease in central arterial stiffness following 12 weeks of total body resistance training with different loads (heavier, 75–90% 1RM; 5 exercise, 3 sets vs. lighter, 30–50% 1RM, 5 exercise 3 sets) in health young men.…”
Section: Discussionmentioning
confidence: 92%
“…Evidence also suggests that resistance training may not have any unfavorable effect on arterial stiffness in middle-aged adults ( Cortez-Cooper et al, 2008 ; Yoshizawa et al, 2009 ). Moreover, a meta-analysis ( Ceciliato et al, 2020 ) and two randomized control trials ( Casey et al, 2007 ; Werner et al, 2019 ) have reported that long-term resistance training (average threee times per week) causes no changes in arterial stiffness among healthy young individuals (average age, 29). Although TRT is effective in improving skeletal muscle mass and function and reversing osteoporosis ( Pollock et al, 2000 ), further studies are warranted to ascertain its effect on arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The included trials in this systematic review and meta-analysis ( n = 20) were intercontinental, published between 2005 and 2020. A majority of the articles ( n = 9) were conducted in Japan ( 17 , 19 , 23 , 35 38 , 40 ), followed by the U.S. ( n = 7) ( 20 22 , 29 , 31 , 33 , 39 ) and each one from Canada ( 18 ), Brazil ( 30 ), England ( 32 ), and New Zealand ( 34 ). Of these, five studies recruited only male participants, seven studies recruited only females, and eight studies recruited a combination of both males and females.…”
Section: Resultsmentioning
confidence: 99%